Differential equations and Laplace transforms: Laplace-transformations
Laplace transforms of differential equations
The Laplace transform of the derivative #f'# of a function #f# can be expressed in the Laplace transform of #f# without the use of derivatives:
Derivative in the time domain If #f# is a differentiable function on #\ivco{0}{\infty}#, the Laplace transform #\laplace{f}# exists, and #\lim_{t\to\infty}\ee^{-st} f(t) = 0#, then \[\mathcal{L} f' (s) = s\cdot (\mathcal{ L}f)(s)-f(0)\]
More generally, if #n# is a natural number, #f# is a piecewise #n#-fold differentiable function, and, for all #k# with #0\le k\lt n#, the limit#\lim_{t\to\infty}\ee^{-st} f^{(k)}(t) = 0# exists, then \[ \laplace{\left(f^{(n)}\right)}(s) = s^n\cdot \laplace{f}(s)-s^{n-1}f(0)-s^{n-2}f'(0)-\cdots-s\cdot f^{(n-2)}(0)-f^{(n-1)}(0)\]
Thanks to this property we can convert a linear differential equation with constant coefficients using Laplace transform into an algebraic equation. By calculating the inverse Laplace transform we can solve the differential equation. For a second order ODE are the operations shown below in a diagram
\[\begin{array}{lcr}f''(t)+p\cdot f'(t)+q = r(t)&{\laplace{}\atop\longrightarrow}& P(s)\cdot\laplace{f}(s) = \laplace{r}(s)\\ \text{solution of }\big\uparrow&&\big\downarrow\text{ solve}\\ f(t) =\mathcal{L}^{-1}(F)(t)&{\mathcal{L}^{-1}\atop \longleftarrow}& \laplace{f}(s) = F(s)\end{array}\]
Below are examples of this solution method.
#x(t) =# # {{50}\over{81}} + {{5 t }\over{9}} -2\cdot \euler^{t} + {{31\cdot \euler^{9 t }}\over{81}} #
In order to find the solution, we write #y=\mathcal{L}(x)#. Then
\[\begin{array}{rcl}
\mathcal{L}(x') (s)&=& s\cdot y(s)-x(0) =s\cdot y(s)+1\\
\mathcal{L}(x'') (s)&=& s^2\cdot y(s)-2s =s^2\cdot y(s)+s-2 \\
\mathcal{L}(-5\cdot t) (s)&=&\displaystyle -{{5}\over{s^2}} \\
\end{array}\]
Therefore, after all terms are moved to the left, the Laplace transform applied to the differential equation \( {{d^2}\over{d t^2}} x-10 {{d}\over{d t}} x+9 x=5 t\) gives
\[-10\cdot \left(s\cdot y+1\right)+s^2\cdot y+9\cdot y+s-{{5}\over{s^2}}-2=0\]
This can be rewritten to
\[\left(s^2-10\cdot s+9\right)\cdot y+s-{{5}\over{s^2}}-12=0\]
Solving this equation with unknown #y# gives
\[ y (s)= {{-s^3+12\cdot s^2+5}\over{s^4-10\cdot s^3+9\cdot s^2}} \]
Partial fraction decomposition of the right-hand side leads to
\[ \begin{array}{rcl}y(s)
&=&\displaystyle {{-s^3+12\cdot s^2+5}\over{\left(s-9\right)\cdot \left(s-1\right)\cdot s^2}}\\
&=&\displaystyle {{50}\over{81\cdot s}}+{{5}\over{9\cdot s^2}}-{{2}\over{s-1}}+{{31}\over{81\cdot \left(s-9\right)}}\\
&=&\displaystyle {{50}\over{81\cdot s}} + {{5}\over{9\cdot s^2}} -{{2}\over{s-1}} + {{31}\over{81\cdot \left(s-9\right)}} \end{array}\]
so linearity of the inverse Laplace transform and determination of the inverse Laplace tansforms of the terms gives:
\[ x (t)= {{50}\over{81}} + {{5 t }\over{9}} -2\cdot \euler^{t} + {{31\cdot \euler^{9 t }}\over{81}} \]
Or visit omptest.org if jou are taking an OMPT exam.